2005
DOI: 10.1152/ajpheart.00912.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38-mitogen-activated protein kinase in adenosine receptor-mediated relaxation of coronary artery

Abstract: Teng, Bunyen, Weixi Qin, Habib R. Ansari, and S. Jamal Mustafa. Involvement of p38-mitogen-activated protein kinase in adenosine receptor-mediated relaxation of coronary artery. Am J Physiol Heart Circ Physiol 288: H2574 -H2580, 2005. First published January 14, 2005 doi:10.1152/ajpheart.00912.2004.-The purpose of this study was to explore the involvement of adenosine receptor(s) in porcine coronary artery (PCA) relaxation and to define the role of MAPK signaling pathways. Isometric tensions were recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
(51 reference statements)
3
14
0
Order By: Relevance
“…It should be mentioned that recent studies on porcine coronary arterial smooth muscle cells have demonstrated an activation of p38 MAPK by PGF 2␣ . PGF 2␣ -induced p38 MAPK phosphorylation occurred rapidly (within minutes), reached a peak at 10 min, and decreased within 60 min (Teng et al, 2005). The ineffectiveness of PGF 2␣ to show an activation of p38 MAPK after 120 min in the present study is consistent with this observation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It should be mentioned that recent studies on porcine coronary arterial smooth muscle cells have demonstrated an activation of p38 MAPK by PGF 2␣ . PGF 2␣ -induced p38 MAPK phosphorylation occurred rapidly (within minutes), reached a peak at 10 min, and decreased within 60 min (Teng et al, 2005). The ineffectiveness of PGF 2␣ to show an activation of p38 MAPK after 120 min in the present study is consistent with this observation.…”
Section: Discussionsupporting
confidence: 91%
“…To examine a possible role of p38 MAPK in the vasorelaxant response to 8, arterial rings with or without endothelium were precontracted with PGF 2␣ (3 M) following a 30-min incubation with SB 203580 (10 M), an inhibitor of p38 MAPK (Teng et al, 2005). Compound 8 (10 M) was administered when the contractile response to PGF 2␣ had reached a plateau.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas adenosine A 2A receptor plays a significant role in background NO release, thus affecting basal coronary tone [32], the role played by adenosine A 2B receptors in NO release remains to be determined. In addition, both adenosine A 2A and A 2B receptors have also been implicated in endotheliumindependent relaxation of coronary artery smooth muscle [37]. In our study, mechanical removal of the endothelium potently reduced the relaxations to NECA, thus indicating that adenosine relaxes pig prostatic arteries through adenosine receptors located on endothelial cells.…”
Section: Discussionsupporting
confidence: 57%
“…A 2A AR involvement with exogenous application of adenosine mediated coronary vasodilation is well established [2,27,33]. A 2A AR mediated NO release is also well recognized in various endothelial cell culture studies, including human, rat and porcine [4,34,35].…”
Section: Discussionmentioning
confidence: 97%